Excellence in Agronomy Initiative Add-on Sampling Strategy - Cole, Steven Michael; Lambrecht, Isabel B.; Iradukunda, Francois; Vandamme, Elke; Chamberlin, Jordan; Tesfaye, K.; Kruseman, Gideon; Saito, Kazuki; Arouna, Aminou; Ragasa, Catherine (CGIAR System Organization, 2023)
A survey tool was developed by the EiA add-on teams for administering by Use Case teams within their areas of implementation. The tool was developed to understand farmer segmentation, gender and generational differences in agricultural management practices and technology adoption, yield gap decomposition and baseline values of key performance indicators in the Use Case population(s) of interest. This information, along with other contextual factors, will inform the design of their Minimum Viable Products (MVPs) to ensure they meet the needs of women, men, youth, and different farmer types and help improve the KPIs of the EiA Initiative. This information can also be used as inputs into ex ante assessments of returns to investment related to the Use Case.